Sequence analysis of the fusion(F) and matrix(M) genes of recen1ly isolated New Castle disease virus from Malaysia - Tan, Sheau Wei; Omar, Abdul Rahman; Ideris, Aini; Yusoff, Khatijah; Tan, Wen Siang (Veterinary Association Malaysia, 2005)
The partial amino acid sequences of fusion (F) and matrix (M) genes encompassing the F cleavage site and the nuclear localization signals, respectively, of 4 recent Newcastle disease virus (NDV) isolates obtained from the field outbreaks between 2000 and 2001 were characterised. Isolates Ol/C, 01/TM and 01/GNS shared the same amino acid sequences at the F cleavage site 111GRRQKRF117.However, isolate OO/IKS has l1lERRQKRFI17 motif at the F cleavage site. Isolate 01/TM also has the highest number of amino acid substitutions at the F gene. Both isolates OO/IKS and Ol/GNS shared 100% amino acid sequence identity at the M gene whilst isolates Ol/C and 01/TM have 3 and 1 unique amino acid substitutions. All the 4 isolates also have 2 unique amino acid substitutions (R200RS and E213D). However, no particularly distinguishing sequence variations were identified among the different NDV pathotypes. All the 4 NDV isolates were grouped into genotype vn with bootstrap value of 90%. The genotype vn comprises the recent NDV strains recovered during the outbreaks between years 1995 and 2001 which have been reported in many countries including China, Taiwan, South Africa and Europe. As the 4 NOV isolates were found phylogenetically related to goose isolate ZJI and pigeon isolate 1307/US/75, they were placed in the same group with bootstrap value of 78 % based on the M gene sequence analysis.